Regional and Multicultural Education in Poland and Ukraine - Andrzej Stępnik; Olena Budnyk; Tetyana Blyznyuk; Piotr Mazur (Vasyl Stefanyk Precarpathian National University, 2017)
Education in Poland and Ukraine are deeply-rooted in multiculturalism, regionalism and patriotic tradition. In the past, these notions were associated with nobility and great national matters. In the era of democratization, modernization and globalization, these notions acquire a new meaning. They influence diverse aspects of everyday life. Therefore, they ought to be updated and based on didactic theory. It is essential for schools which realize regional, cultural and European educational paths. Formation of educational space of modern educational institutions on the basis of regionalism and multiculturalism is effective for obtaining the following pedagogical principles: nature accordance, culture compliance, humanism, nationalism, multiculturalism, tolerance, harmony between family and school education and others. The authors focus on theoretical reflection.